PENGARUH MOTIVASI BELAJAR DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 5 PALU - Nurdiana Nurdiana; Anggraini Anggraini; Gandung Sugita; I Nyoman Murdiana (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to see how the effect of learning motivation and interest in learning on student math learning outcomes. This research was conducted at SMP Negeri 5 Palu. This research is an ex-post facto research. The population in this study were all VIII grade students of SMP Negeri 5 Palu in the 2023/2024 school year totaling 95 people. The sampling technique used was proportional sampling. The sampling technique used was simple random sampling with a sample of 33 students. Data collection was obtained through a questionnaire of learning motivation, a questionnaire of interest in learning, and the value of students' math uas results. The results of hypothesis testing show that at a significance level of 5% (1) sig value (0.000) < (0.05) then H_0 is rejected, so it can be concluded that there is a significant effect of learning motivation on the mathematics learning outcomes of students in class VIII SMP Negeri 5 Palu by 76.1% (2) sig value (0.000) < (0.05) then H_0 is rejected, so it can be concluded that there is a significant influence of learning interest on the mathematics learning outcomes of VIII grade students of SMP Negeri 5 Palu by 39.6% (3) sig value (0.000) < (0.05) then H_0 is rejected, so it can be concluded that there is a significant influence of learning motivation and learning interest of VIII grade students of SMP Negeri 5 Palu by 81.5%..